A national cross-sectional study on the influencing factors of low HPV vaccination coverage in mainland China - Xiangju Yin; Mengrui Zhang; Fei Wang; Yue Huang; Yuyao Niu; Pu Ge; Wenli Yu; Yibo Wu (Frontiers Media S.A., 2023)
BackgroundHPV vaccine can block the infection of high-risk human papillomavirus and is an important measure to effectively reduce the incidence of cervical cancer and precancerous lesions. However, the HPV vaccination rate is still low in China. There are many factors. Therefore, it is important to study the influencing factors to provide basis for promoting the formulation of vaccination strategies.MethodsThis study used a multi-stage sampling method to conduct a face-to-face questionnaire survey on women in different regions of China. The new general self-efficacy scale was used to measure the self-efficacy of the respondents. The short form of family health scale measured their family health. The t-test and binary Logistic regression analysis were used to screen the influencing factors of HPV vaccination. Restricted cubic spline model was used to analyze the influence trend of self-efficacy and family health on HPV vaccination rate.Results(1) The HPV vaccination rate was low, especially in the ≤18 group. The place of residence, capita household income/month, individual self-efficacy and family health had a significant impact on HPV vaccination. (2) The restricted cubic spline model showed that self-efficacy positively promoted HPV vaccination, the correlation strength was statistically significant (χ2 =27.64, P<0.001) and non-linear (χ2 = 12.49, P = 0.0004); The poor family health hindered HPV vaccination, and the association strength was statistically significant (χ2 = 47.81, P < 0.001) and non-linear (χ2 = 9.96, P = 0.0016).ConclusionIt is necessary to strengthen the health education of HPV vaccination knowledge in the population to eliminate the hesitancy of vaccination. Free HPV vaccination strategies should be developed and encourage people of appropriate age to receive as early as possible. Self-efficacy and family health should be enhanced to increase HPV vaccination rate, so as to achieve the goal of reducing the incidence of cervical cancer and protecting women's health.